Learning styles and their relationship to discovery behavior among university students (Mustal) - Khalid, Prof.Dr. Hassan Fakhruddin; Mohammed, Aras Osman (Sulaimani Journal for Humanities, 2026)
The aim of this study is to determine the level of learning styles and discovery behavior among students in general, to determine the differences between them according to gender and specialty variables, to determine the level of relationship between learning styles and discovery behavior. The sample of the study (934) male and female students were randomly selected from the appropriate Chinese. The tools used are the measure (learning styles) the researcher himself based on the areas of the Kolb model for learning styles through open surveys The most important statistical tools used are (arithmetic mean, standard deviation, Pearson, T-test). The results showed that the level of learning styles and discovery behavior among students of Sulaimani University is high. There is a statistical difference in the level of learning styles and discovery behavior according to gender in favor of females Each of them increases the level of the other and vice versa. Finally, the researcher made some recommendations in the light of the results.
Keywords: Learning styles; behavior; discovery behavior; university student